TNI’s Role in Counterterrorism: Impact On Military Reform - Anindya, Chaula (2017)
Lawmakers in Indonesia are currently revising an existing anti-terrorism law. The proposed legislation will give TNI, the Indonesian armed forces, a more direct role in combatting terrorism. This may pose a hurdle to continued military reform.